Evaluasi Model CIPP pada Program Kewirausahaan di Sekolah Menengah Atas - Afifahtul Mukarromah, Siti; Sholeh, Muhamad; Riyanto, Yatim (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The problem of unemployment is one of the problems that has not yet been resolved. The open unemployment rate for high school graduates is 8.15%, second only to vocational school graduates. Entrepreneurship programs implemented in high schools are one option to reduce unemployment rates. Through the entrepreneurship program, students are taught how to become entrepreneurs so that entrepreneurial characters are also instilled. The hope is that students will be able to become creative, independent individuals and be able to take advantage of existing opportunities. Entrepreneurship programs need to be evaluated to measure their achievements. The research uses an evaluative model with the SLR approach. Evaluation using the CIPP model is a comprehensive evaluation model. The CIPP model evaluation includes 4 components, namely, context, input, process, and product. Based on the results of research using the SLR approach, the entrepreneurship program in high school is quite good. Entrepreneurship programs in high schools need to be continued with improvement and development.